Weak polynomial topology and weak analytic topology on Banach spaces and on Freshet spaces - Zagorodnyuk, A.V.; Mytrofanov, M.A. (Carpathian Mathematical Publications, 2012)
We investigate under which conditions weak polynomial or weak analytic topology (*-weak polynomial or *-weak analytic topology) coincides whith the norm topology on a real (complex) Banach or Freshet space.